2011
DOI: 10.4103/0970-9290.87061
|View full text |Cite
|
Sign up to set email alerts
|

Tobacco cessation and counseling: A dentists′ perspective in Bhopal city, Madhya Pradesh

Abstract: Monitoring of effective planning and execution of these programs by appropriate authorities at regular intervals is vital for successful achievement of the goal of "Tobacco Free Society."

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 0 publications
0
22
0
Order By: Relevance
“…Most dentists had a good attitude towards the domains Ask (81.2%), Advise (89.6%), Assess (66.8%), Assist (79.2%) and Arrange (69.2%). Studies in Malaysia, India, Hong Kong, Saudi Arabia and Islamic Republic of Iran reported that most dentists had an encouraging attitude towards providing tobacco cessation advice to their patients (7,8,13,15,16,21). In contrast, a similar study conducted in the United States of America (USA) reported that only 58% of dentists had a positive attitude (22).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Most dentists had a good attitude towards the domains Ask (81.2%), Advise (89.6%), Assess (66.8%), Assist (79.2%) and Arrange (69.2%). Studies in Malaysia, India, Hong Kong, Saudi Arabia and Islamic Republic of Iran reported that most dentists had an encouraging attitude towards providing tobacco cessation advice to their patients (7,8,13,15,16,21). In contrast, a similar study conducted in the United States of America (USA) reported that only 58% of dentists had a positive attitude (22).…”
Section: Discussionmentioning
confidence: 98%
“…Most dentists believe it to be their responsibility to help their patients with tobacco cessation or to prevent tobacco use. A study in India showed that 98.7% of dentists felt that they were responsible for providing tobacco cessation advice, and 94.7% reported that they were confident in providing tobacco cessation advice to their patients (7)(8)(9)(10)(11)(12). A study among dentists in Kelantan, Malaysia showed that 72.7% were confident in giving such counselling.…”
Section: Introductionmentioning
confidence: 99%
“…To address these issues, many experts have argued that TCC should be included in the curriculum of dental schools, and studies have reported the attitudes and knowledge about TCC among dental students 16 23 and dentists 15 , 24 , 25 . Training in TCC has been incorporated into the curricula of most U.S. dental schools 23 , 26 and dental schools in other countries 18 , 21 .…”
mentioning
confidence: 99%
“…Studies have shown that oral health professionals perceive Tobacco cessation as a part of their services to their clients (Monaghan, 2002;Walsh and Ellison, 2005;Amit et al, 2011). In their Consensus Report of the 2nd European Workshop on Tobacco Use Prevention and Cessation for Oral Health Professionals, have outlined provision of basic, intermediate and advanced care for helping patients quitting Tobacco use that are specific for dental team members.…”
Section: Introductionmentioning
confidence: 99%